The Internationalization of Chinese Firms: Entry Mode Choice - Zhang, Xu (2010)
Chinese firms and other emerging markets firms aim to select a favourable entry mode to start or expand their international business, thus this is significant issue for research. This study demonstrates that the Chinese firms’ choice of entry mode is determined by internal-factors, external-factors and transaction cost factors. This is illustrated through the investigation of a case study of the Haier Group’s choice of entry mode and internationalization. Therefore, four processes of choice of entry mode and an extended framework are presented to evaluate the determinants of Chinese firms’ choices of entry mode, which are highly recommended for other emerging market companies.